Building a sharable literature collection to advance the science and practice of implementation facilitation - Ritchie, Mona J.; Smith, Jeffrey L.; Kim, Bo; Woodward, Eva N.; Kirchner, JoAnn E. (Frontiers in Health Services, 2024)
Background Implementation science seeks to produce generalizable knowledge on strategies that promote the adoption and sustained use of evidence-based innovations. Literature reviews on specific implementation strategies can help us understand how they are conceptualized and applied, synthesize findings, and identify knowledge gaps. Although rigorous literature reviews can advance scientific knowledge and facilitate theory development, they are time-consuming and costly to produce. Improving the efficiency of literature review processes and reducing redundancy of effort is especially important for this rapidly developing field. We sought to amass relevant literature on one increasingly used evidence-based strategy, implementation facilitation (IF), as a publicly available resource. Methods We conducted a rigorous systematic search of PubMed, CINAHL, and Web of Science citation databases for peer-reviewed, English-language articles with “facilitation” and a combination of other terms published from January 1996 to December 2021. We searched bibliographies of articles published from 1996 to 2015 and identified articles during the full text review that reported on the same study. Two authors screened 3,168 abstracts. After establishing inter-rater reliability, they individually conducted full-text review of 786 relevant articles. A multidisciplinary team of investigators provided recommendations for preparing and disseminating the literature collection. Findings The literature collection is comprised of 510 articles. It includes 277 empirical studies of IF and 77 other articles, including conceptual/theoretical articles, literature reviews, debate papers and descriptions of large-scale clinical initiatives. Over half of the articles were published between 2017 and 2021. The collection is publicly available as an Excel file and as an xml file that can be imported into reference management software. Conclusion We created a publicly accessible collection of literature about the application of IF to implement evidence-based innovations in healthcare. The comprehensiveness of this collection has the potential to maximize efficiency and minimize redundancy in scientific inquiry about this strategy. Scientists and practitioners can use the collection to more rapidly identify developments in the application of IF and to investigate a wide range of compelling questions on its use within and across different healthcare disciplines/settings, countries, and payer systems. We offer several examples of how this collection has already been used.